Tradeoffs for the poor, divine coincidence for the rich - Marco Del Negro; Ibrahima Diagne; Keshav Dogra; Pranay Gundam; Donggyu Lee; Brian Pacula (Federal Reserve Bank of New York, 2025)
We use an estimated medium-scale HANK model to investigate how the tradeoff between stabilizing inflation and consumption volatility varies for households with different levels of wealth. Consumption for the rich is mostly affected by demand shocks via their exposure to highly procyclical profits-for them, stabilizing consumption and inflation coincide. The poor are more vulnerable to supply shocks, hence aggressively stabilizing inflation is costly in terms of their consumption volatility. While they dislike inflation because it erodes real wages, they are hurt even more by an aggressive monetary policy response to inflation, which reduces real wages further while increasing unemployment.
Keywords: E12; E31; E52; E58; 330; inflation; inequality; monetary policy; HANK models